Mapping Of Consumption Of Green Products For Urban Society Denpasar City - A.A.Ketut AYUNINGSASI; Amrita Nugraheni SARASWATY (Indonesia Strategic Sustainability, 2022)
One of the points of the 2030 sustainable development goals is to ensure sustainable production and consumption patterns. One strategy that can be used is to consume food and non-food based on pro-environment (green product). This study aims to determine how the consumption pattern of green products from urban communities in Denpasar City. What are the internal and external factors that encourage urban communities in the city of Denpasar to consume green products? The analysis used in this research is descriptive analysis which is useful for looking at the average, cross tabulation of demographic factors, internal and external factors with the choice of consuming green products from the urban community of Denpasar. The results of the study stated that the factors that became the basis for people to consume green products were 1) the desire to adopt a more environmentally friendly lifestyle, 2) health factors, 3) better quality of goods, and 4) following trends. Types of Green Products consumed by respondents include: eco bags, drinking water bottles, straws, tablespoons, bath soap, organic vegetables and fruits, lunch boxes, snacks, cosmetics, and mineral water. Public awareness of the city of Denpasar is becoming a trend in the implementation of achieving sustainable development goals.